Internalisasi Nilai-Nilai Islam Moderat Melalui Pendidikan Aswaja di MTs. Mamba`us Sholihin Hollo-Amahai Maluku Tengah - Ramadhan Wahyu Setiawan; Muhammad Shohib (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine the process of internalization of moderate Islamic values ​​through Aswaja education at MTs Mambaus Shollihin, Hollo-Amahai, Central Maluku. The research method used is qualitative descriptive with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation related to educational activities at MTs Mambaus Shollihin. The research subjects consisted of the principal, teachers, students, and local community leaders. Data analysis was carried out inductively with the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the internalization of moderate Islamic values ​​at MTs Mambaus Shollihin is carried out through three stages: value transformation, value transaction, and value transinternalization. The value transformation process is carried out through the delivery of educational materials that emphasize the principles of moderate Islam, such as tawasuth (moderate), tawazun (balanced), i'tidal (fair), tasamuh (tolerance), and musawah (equality). The implications of this study indicate that Aswaja education at MTs Mambaus Shollihin is effective in forming moderate characters in students, which are expected to contribute to the creation of a peaceful, tolerant, and diversity-appreciating society. The recommendations from this study are the need to strengthen the education curriculum that emphasizes moderate values, and increasing the role of families and communities in supporting education based on moderate Islamic values.